Evaluasi Implementasi Program Keluarga Harapan Untuk Mengurangi Angka Kemiskinan di Indonesia - Darmin Tuwu (DIALEKTIKA PUBLIK, 2026)
This study aims to evaluate the implementation of the Program Keluarga Harapan (PKH), in Sawa Village, Sawa District, North Konawe Regency, Southeast Sulawesi Province. Using a qualitative case study approach, data were collected through in-depth interviews, participant observation, and document analysis involving beneficiary families, program facilitators, local officials, and community leaders. The study applies a policy evaluation framework focusing on effectiveness, targeting accuracy, compliance, and program impact. The findings reveal that PKH has contributed significantly to reducing the financial burden of poor households, particularly in accessing education and healthcare services. However, several critical challenges remain. First, targeting inaccuracies persist, as evidenced by inclusion and exclusion errors due to outdated and less adaptive social welfare data. Second, beneficiaries’ compliance with program conditions tends to be administrative rather than substantive, limiting behavioral change outcomes. Third, the limited number and capacity of program facilitators affect the quality of assistance and monitoring processes. Fourth, while PKH effectively functions as a short-term social protection mechanism, its impact on long-term economic empowerment remains limited. Additionally, issues of transparency, community participation, and weak monitoring systems hinder optimal program performance. The study concludes that the effectiveness of PKH is not solely determined by its policy design but also by implementation quality, institutional capacity, and local socio-economic context. Strengthening data systems, enhancing facilitation, integrating empowerment programs, and improving governance are essential to maximize program outcomes. This research contributes to the development of evidence-based social protection policies, particularly in improving conditional cash transfer programs in localized contexts.